1976
DOI: 10.1099/00221287-96-1-125
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Uptake and Metabolism of Soluble Carbohydrates by the Rumen Ciliate Dasytricha ruminantium Isolated from Ovine Rumen Contents by Filtration

Abstract: A filtration technique is described whereby metabolically-active suspensions of Dasytricha ruminantiurn can be isolated from rumen contents with negligible contamination by bacteria or other protozoa. The effects of environmental factors and of the diurnal cycle of the rumen on the uptake and metabolism of soluble carbohydrates by these isolated cells were examined. The principal contribution of the protozoan metabolic end-products to the host ruminant is the supply of lactic, acetic and butyric acids during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 19 publications
0
53
0
Order By: Relevance
“…Hydrogen and carbon dioxide are metabolic products of anaerobic metabolism of both bacteria (Bryant 1977;Wolin 1979) and protozoa (Abou Akkada and Howard 1960;Prins and Prast 1973;Williams and Harfoot 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen and carbon dioxide are metabolic products of anaerobic metabolism of both bacteria (Bryant 1977;Wolin 1979) and protozoa (Abou Akkada and Howard 1960;Prins and Prast 1973;Williams and Harfoot 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The studies reported here were undertaken to (a) confirm the origin and location of the invertase and examine the range of extracellular carbohydrase activity associated with the holotrich protozoa and (b) assess the effect of nutritional and environmental factors on exocellular invertase formation. Certain aspects of this work have been reported previously (33).…”
mentioning
confidence: 69%
“…Further, SBC itself may be an intrinsic factor promoting co-evolution. Rumination is a thermally intensive process: rumen temperatures during active digestion can reach upwards of 46 ° C but typically range between 39 and 42 ° C [Dale et al, 1954;Hungate, 1968;Williams and Harfoot, 1976;MacDonald, 1984;Williams, 1986;Moran, 2005;Beatty et al, 2008aBeatty et al, , 2008bSigner et al, 2010;Turbill et al, 2011]. Semi-reversible damage to neurons and cortical impairment begin at similar temperatures -40 to 41 ° C [Gwozdz et al, 1970[Gwozdz et al, , 1978Millan et al, 1979;Gold et al, 1985]; thus, SBC may be a prerequisite for FF on both physiological and evolutionary scales.…”
Section: Discussionmentioning
confidence: 99%